Wayward Jews, God-fearing Gentiles, or Curious Pagans? Jewish Normativity and the Sambathions - Cornthwaite, Christopher J. (2017)
One of the most influential collections of Jewish material evidence in the last century, Corpus Papyrorum Judaicarum, includes Victor Tcherikover’s well-known work on the Sambathions, based on the common appearance of proper names, groups, and deities with similar, Sambath- roots. At stake was whether these people were Jews and the ways in which diaspora Jews and their host communities influenced one another. This historiographical study draws upon the recent category shift from Jewish to Judaean to argue that Tcherikover focuses on religious observance to test whether people with unknown origins are Jews. By doing so, he rejects that many of the Sambathions are Jews and shifts the evaluation of questionable behavior towards gentiles and God-fearers, thus inadvertently using gentiles to create and/or reinforce Jewish normativity.
Keywords: Synagoge; Frühjudentum; Heidentum; Normativität; Ethnizität; Religion; Handschrift; Epigraphik; Categories -- religion -- ethnicity -- Tcherikover -- Judaeans -- papyri -- inscriptions -- onomastics